Terrestrial influence on the late Cretaceous Tethyan-Atlantic Epeiric Sea in the Yola Basin, Northern Benue Trough, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
A multi-proxy investigation was carried out on three outcrop sections from the Upper Cretaceous Numanha Formation extended in the Yola Basin of the Northern Benue Trough, Nigeria. The Numanha Formation is a predominantly shale sequence that preserves the Turonian–Coniacian depositional history of the Atlantic and shallow southern Tethyan seaway. The investigation included palynofacies characterization of the sedimentary organic matter content of 61 samples collected from three sections, NL10, NL8, and NL4, in addition to analyses for the total organic carbon (TOC) and carbon:nitrogen (C/N) ratios in 44 samples from all of the three studied sections. Palynofacies data confirms an overall marginal marine (estuarine) depositional setting for the Numanha Formation which was strongly impacted by terrestrial and freshwater sources. This is based on the following observations: 1) near-constant presence of marine dinoflagellate cysts and/or benthic planispiral microforaminiferal inner linings, 2) strong terrestrial contribution of transported vascular plant fragments such as opaque, structured, and degraded phytoclasts with fluxes of cuticles at certain intervals, 3) near-constant presence of the freshwater alga Pediastrum which was also recorded in high proportions at certain intervals. TOC content for the majority of the analyzed samples was generally low (